2021
DOI: 10.1186/s12889-021-11197-7
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors associated with acceptance of COVID-19 vaccine and clinical trials in Uganda: a cross-sectional study in western Uganda

Abstract: Background Health experts agree that widespread use of safe and effective vaccines will rapidly contain the COVID-19 pandemic. The big question is whether these vaccines can easily be accepted by their end-users. Our study aimed at determining sociodemographic factors associated with acceptance of vaccines and clinical trials of COVID-19 in western Uganda. Method A simplified snowball sampling technique was used to select 1067 respondents of 18–70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(109 citation statements)
references
References 20 publications
6
100
3
Order By: Relevance
“…Data from Nigeria from March to September 2020 show a positive, increasing trend in vaccine acceptance among this population. Studies from Uganda show that the willingness to participate in COVID-19 vaccine trials is considerably lower among the general population [98] compared with the healthcare professionals [99] (44.6% vs. 70.2%, respectively). Interestingly, two studies conducted during the same period of time (during the initiation of the immunization process in Uganda) showed considerably different rates of people's intention to receive the vaccine, with sufficiently lower rates observed in the population of medical students [100] 37.3%, compared with 70.1% observed among the general population.…”
Section: Resultsmentioning
confidence: 99%
“…Data from Nigeria from March to September 2020 show a positive, increasing trend in vaccine acceptance among this population. Studies from Uganda show that the willingness to participate in COVID-19 vaccine trials is considerably lower among the general population [98] compared with the healthcare professionals [99] (44.6% vs. 70.2%, respectively). Interestingly, two studies conducted during the same period of time (during the initiation of the immunization process in Uganda) showed considerably different rates of people's intention to receive the vaccine, with sufficiently lower rates observed in the population of medical students [100] 37.3%, compared with 70.1% observed among the general population.…”
Section: Resultsmentioning
confidence: 99%
“…In South Africa, vaccine acceptance rates were assessed in nine surveys showing rates varying between 52 and 82% [ 15 ]. In other African countries, vaccine acceptance rates were 88% in Egypt [ 16 ] and 74.5% in Nigeria [ 17 ] but only 54.1% in Ghana [ 18 ], 53.6% in Uganda [ 19 ], and 46.1% in Ethiopia [ 20 ]. Of the eight studies conducted among healthcare workers, three surveys reported vaccine acceptance rates below 60%, with the lowest acceptance rate in the DRC (27%) [ 11 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a French study found a vaccine hesitancy among the working-age population ranged from 9.3% to 43.2%, depending on the vaccine characteristics [21] . Besides, from a developing country perspective, a study from Uganda on the acceptance of the COVID-19 vaccine found a low level of interest for vaccine and clinical trial interest [22] . In the United States, Viswanath et al have concluded in their study that Race/ethnicity, risk perceptions, exposure to diverse media for COVID-19 news, party identity, and trust in scientists were found as variables influencing COVID-19 vaccination uptake [23] .…”
Section: Introductionmentioning
confidence: 99%